MORE Is Better Leading Operations with Meaning, Optimism, and Relationships for Excellence. - Miller, Kathy (Productivity Press, 2025)
This book is essential reading for anyone in leadership within the manufacturing sector, from executives to operational managers. At a time when the manufacturing sector is navigating global competition and technological upheaval, this book serves as a hopeful roadmap.